1965
DOI: 10.1104/pp.40.3.458
|View full text |Cite
|
Sign up to set email alerts
|

Relative Kinetics of Chlorogenic and Caffeic Acids During the Onset of Boron Deficiency in Sunflower

Abstract: -\ characteristic lesion, indicative of )oron dleficiencv in plants, is the appearance of necrotic areas in wvhich a blue-white finiorescenice may oftenl be note (d (3). In the stinflower. the filuorescenlce has l)een shown to restilt primarilv from CA2 and CG.\ acids (2). The latter were estimatedl to l)e as high a-s I () times niorimial valuies in the greeni areas contigtnotus With the necrotic. As it is conceival)le that the necrosis itself restilts fromil excess phenolic acids. we have (leterilinled the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1967
1967
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…2) in other plant species when B deficient (13,21,42). These results also are reflected in the activity of polyphenol oxidase (Fig.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…2) in other plant species when B deficient (13,21,42). These results also are reflected in the activity of polyphenol oxidase (Fig.…”
Section: Resultsmentioning
confidence: 52%
“…Therefore, it was argued that a B deficiency favored the pentose phosphate pathway which would result in the accumulation of phenolic compounds (21). Indeed, some have indicated the accumulation of certain phenolic and flavonoid compounds in the tissue due to B deficiency (5,9,13,29,41,42).…”
Section: Introductionmentioning
confidence: 98%
“…The positive effect of Zn has been previously reported on total phenolic contents (48,49). Authors have suggested that this increase is resulted from increased expression of responsible genes for biosynthesis of phenolic compounds (50). Total phenol content increased with the application of sulfur fertilizer.…”
Section: Discussionmentioning
confidence: 67%
“…resulted in an induced fluorescence ofthe stem tissue, a response that Spurr (1952) suggested was due to an increased level of caffeic and chlorogenic acids. Others (Dear and Aronoff, 1965) suggested that the increase in caffeic acid caused tissue necrosis; caffeic acid or its metabolite caused a breakdown of conductive tissue in the plant, bringing about death of the tissue. Others have also observed the accumulation of fluorescent products, presumably phenols, in boron-deficient plants (Watanabe et at., 1961(Watanabe et at., , 1964Shkol'nik, 1974;Rajaratnam and Lowry, 1974).…”
Section: Phenolsmentioning
confidence: 99%